簡析老子的生命倫理觀及其現代意蘊: A Sense of Bioethics from Laozi - YANG, Tianming (International Journal of Chinese & Comparative Philosophy of Medicine, 2007)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 從現代生命倫理觀研究的現實出發，解析老子關於生命倫理觀的思想精髓及其現代意蘊，對於理解與認識現今社會發展中人與自然、人與社會和人與人之間關係所存在的問題，對於促進社會中人自由而全面的發展，都具有重要的價值和意義。 從中國傳統思想文化出發，依託社會發展的現實，從倫理學角度對生命的解讀就不能僅僅局限於醫學領域，而應該是在社會這一更為寬泛的領域中進行研究。老子的思想深刻地揭示了自然、人以及社會存在和發展的內在規律，他的思想閃耀著獨特的人性的、智慧的光芒。在其博大深遠的思想之中顯現若現代意義的關於生命倫理觀的意蘊，其基本思想是：人的存在和發展必須是基於對自然和社會發展本質規律（“道”）的深入認識以及積極能動地尊重和適應﹔人的生命價值的實現和生命尊嚴的獲得必須是基於人與自然和社會良好的互動關係中得以實現的。 人與外在因素互動過程中， 基本上形成了人與自然、人與社會和人與人之間三個層次的關係。在人與自然的關係中， 老子認為天之道也即是人之法，自然法則也應是人的行為規範， 應把對自然法則的認識上升到人類行為價值的高度。人對自我生命的愛護、尊重與保全，是以尊重與遵循自然之道為前提的，人的生命的存在與發展必須與自然保持和諧統一。 在人與人的關係中， 老子首先認為在對待他人的利益方面，應該做到以寬厚仁慈的心態待人接物，成人之美，與人為善。其次，老子強調的是個體對自我心態和行為的約束。再者，在對待與他人的矛盾方面，老子認為“夫唯不爭，故天下莫能與之爭”。 在分析社會與人的關係中，老子首先認為國家政策的實施，應該是循序漸進的，必須考慮到普通人的承受能力。其次老子認為社會和政府必須協調、平衡人與人之間的各種差距，政策的制定與實施應盡可能關照到最大多數人的利益。再者老子認為社會中人與人利益的不均衡，必將致使社會存在風險。 老子的思想對於我們今天從倫理的角度認識人生命的尊嚴、權利與價值，對於理解人以及社會的和諧發展都具有重要的現實意義和價值。 第一、隨著經濟的快速發展，人類對自然環境的破壞也日漸加劇。人類存在和發展的權利與自然是平等的，不能以犧牲生態環境、犧牲人生命存在和發展的價值去發展經濟，因為社會的可持續發展依存於人類與自然的和諧統一。 第二、目前社會發展存在諸多方面的不均衡狀態。政府有責任縮小包括經濟、醫療和教育等方面的差距，使得公眾在各種資源的佔有上盡可能地趨向均衡狀態，使公眾擁有相對平等的生存權、發展權、生命健康權和接受教育的權利等，以維護其生命的尊嚴和促進其生命價值的實現。 第三、在醫學活動中，其正實踐“預防為主”的方針，有效控制和消除引發疾病的各種自然和社會的因素，激發人自身的潛能，順應生命存在與發展的自然和社會的內在規律，引導公眾崇尚並踐行健康、文明、科學的生活方式，在“預防為主”科學理念的引領下積極維護人的生命健康權。 第四、個體人文素質的提高是社會文明發展的重要標誌，它能夠促進人與人之間關係的協調，能夠喚醒和增強個體關注與維護他人生命的尊嚴、權利、價值。重視優良傳統道德文化在社會中的作用與價值，以制度化的方式加強優秀傳統道德文化的教育和實踐，培養公眾的人文主義精神。 以社會現實為基礎，從生命倫理觀的角度出發對老子思想的研究，必然能夠加深對人以及生命的尊嚴、權利、價值的維護與實現的理解，促進人與自然、社會的和諧發展，促進人自由而全面的發展。 This paper attempts to show that Laozi’s thought covers a sense of bioethics and carries profound moral implications for contemporary society. His basic thought includes: Human existence and development must be based on the essential rule of nature (dao); a thorough understanding of dao can improve human adaptation; and human value and dignity must be realized based on natural and good social relations and interactions. In natural relations, Laozi thought that the dao of nature is also the rule of person; that is, natural rule should also be a person’s behavior standards. Human existence and development must maintain a harmonious unification with nature. In personal relations, Laozi thought that one should treat other people generously and beneficially, helping others do well. At the same time, Laozi emphasized that one must control and restrict one’s desires and passions. As he put it, "if you do not compete with anyone else, nobody will defeat you." Laozi’s thought has good ethical implications for today. First, along with fast economical development, humans should pay attention to the preservation of the natural environment. Society’s sustainable development depends on a harmonious human unification with nature. Second, government should have a responsibility to maintain harmonious relations among different classes and areas of human persons. Third, in medical activity, preventive medicine, rather than aggressive procedures, should be taken as the main medicine. Finally, seriously research into Laozi’s thought for the sake of bioethical studies can significantly deepen our understanding of humans, nature and development. DOWNLOAD HISTORY | This article has been downloaded 73 times in Digital Commons before migrating into this platform.